Model Pembelajaran Contextual Teaching Learning (CTL) pada Sekolah Dasar - Desy Rusminawati Amijaya; Iis Ristiani (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This research is a preliminary research that contains efforts to apply the contextual teaching learning model at the elementary school level. This study also aims to determine student responses to the application of the contextual teaching learning model in grade 4 students of SD Negeri Pangestu. This study uses a research design with a "One Shot Case Study" design, which is research conducted by giving certain treatment to research subjects, in this case the contextual teaching learning model. The data obtained were then analyzed using research methods to the students. In this study, researchers used questionnaire data collection techniques. The questionnaire data used in this study was student motivation data. From data processing, research results were obtained which showed that student responses to learning with the contextual teaching learning method received a positive response from students with 9.0.82% of students liking to follow learning with the CTL model. And 87.90% of students agree that the CTL learning model is applied to Indonesian language learning in the future.